2004
DOI: 10.1063/1.1765200
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent oxygen-related electronic states in silicon nanocrystals

Abstract: Silicon nanocrystals embedded in SiO 2 were isolated with a selective etching procedure, and the isolated nanocrystals' excitonic emission energy was studied during controlled oxidation. Nanocrystals having initial diameters, d 0 , of ϳ2.9-3.4 nm showed a photoluminescence ͑PL͒ blueshift upon oxidatively induced size reduction, as expected from models of quantum confinement. Oxidation of smaller Si nanocrystals ͑d 0 ϳ 2.5-2.8 nm͒ also initially resulted in a PL blueshift, but a redshift in the PL was then obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
4
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 16 publications
2
64
4
1
Order By: Relevance
“…29 In previous investigations of Si-NCs fabricated by other techniques, it has been found that oxidation may also result in a redshift of the NCs photoemission. 26,30,31 Theoretical calculations indicate that this could originate from the introduction of intragap energy levels by interfacial Si=O bonds, 26,27,32 and Si-O-Si surface bridges.…”
mentioning
confidence: 99%
“…29 In previous investigations of Si-NCs fabricated by other techniques, it has been found that oxidation may also result in a redshift of the NCs photoemission. 26,30,31 Theoretical calculations indicate that this could originate from the introduction of intragap energy levels by interfacial Si=O bonds, 26,27,32 and Si-O-Si surface bridges.…”
mentioning
confidence: 99%
“…A similar HF etching procedure was recently employed to study the photoluminescence behavior of free standing Si nanocrystals. 3 Transmission electron micrographs of embedded nanocrystal samples demonstrate that nanocrystals are spherical with an average size of 5.1 nm and a distribution full width at half maximum (FWHM) of 3.9 nm [ Fig. 1(a)].…”
mentioning
confidence: 99%
“…It is likely that for the nanocrystal size range investigated here (average diameter > 3 nm), luminescence originates from size-dependent oxygen-related defect centers at the nanocrystal/matrix interface rather than from confined excitons within the nanocrystal. [12] Further studies are underway on larger nanocrystals, which can be obtained by annealing at higher temperatures, to determine the effect of oxygen dose on confinement-based luminescence.…”
Section: Resultsmentioning
confidence: 99%